Decoding Sentiments: Exploring Islamic Fintech Discourse on Twitter in The Post-Pandemic - Haidar, Abdullah; Hendrasto, Nur; Herindar, Evania; Chairiyati, Fauziah (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
Twitter (later called X) users' perceptions of sharia-compliant fintech offer a revealing insight into their responses to Islamic financial innovations. Analyzing 3,231 tweets, the study found that the majority of attitudes were neutral (55,6%), followed by positive sentiments (33,3%), and negativity was the least (11,1%). This paints an intriguing picture of user reactions toward Islamic fintech. The prevalence of neutral attitudes suggests a lack of full engagement or a neutral stance among users, potentially due to limited understanding or minimal interaction with Islamic finance platforms. However, the significant positive sentiment indicates an interest and endorsement of sharia-compliant finance, seen as an ethical and aligned alternative within Islamic principles. Conversely, the emergence of negative sentiment raises concerns regarding compatibility with genuine sharia principles and the safety of its implementation. Addressing these concerns, education and transparency become crucial. A comprehensive approach involving regulation, outreach, and risk management is essential to build trust and understanding of the value sharia fintech offers in the modern financial landscape. Keywords: Fintech, Sentimen fintech syariah , Twitter, Covid-19